Peran dan Potensi Green Economy terhadap Kesejahteraan dan Pemberdayaan Masyarakat Lokal - Zikri Rahman; Marliyah; Nur Ahmadi Bi Rahmani (SAFE-Network, 2023)
Green economy is an economic approach that focuses on sustainable and environmentally friendly economic growth. The presence of Nukny Funland Water Park Ecotourism in Percut Sei Tuan sub-district, Deli Serdang district, North Sumatra, which is a green economy-based tourist spot in its management while having an impact on the community's economy. The purpose of this study was to determine how the role and potential of the Green Economy on the welfare and empowerment of local communities, increase their income, and preserve the environment through this Nukny Funland ecotourism. This research uses a qualitative method, where the data used in this study comes from observations and interviews with workers, visitors and the community. The results showed that ecotourism has managed with the concept of green economy quite well and has a positive impact on income and provides new economic opportunities for the community.